Acoustic tracking of juvenile cod (Gadus morhua) in Skagerrak : Effects of body size on short-term movement patterns in nearshore habitats - Thoresen, Adine Guldborg (2008)
The coastal cod is an important commercial and recreational resource for the local communities in the Skagerrak. The situation of this and neighbouring stocks has worsened for decades, promoting an imperative need for better knowledge of the fine-scale ecology and behaviour of the species. In this study, the home ranges and vertical movement pattern of nearshore juveniles (n = 20, length = 325 mm [mean]; 265 - 375 mm [range]) were investigated using acoustic telemetry and kernel density estimators. In addition, habitat preferences were estimated by use of resource selection functions. In concordance with the hypotheses, home range sizes increased with fish length, whereas bigger fish remained at shallower depths than smaller fish. Although inconclusive, results were indicative of smaller fish displaying greater variation in vertical movement than larger fish. The fish used habitats disproportionately to what was available, and although tests were not significant the results showed a clear trend of selecting barren habitats over more complex habitat structures. These behavioural patterns are thought to reflect a dynamic decision-making process where intra- and inter-specific competition and predation pressure drive the selection of the trade-off between shelter and forage. Further, these results show that the classification of important habitats for a commercially exploited species is a complex process that should be investigated on a broader scale.